(untitled) (Journal of Educational Sciences, 2020)
It is examined the content structure of the subject “Self-сognition” in the context of the updated content of education in general education schools in the article. The analysis of textbooks and educational- methodical complexes of the subject is carried out, the authors give a methodological description of the 6th grade textbook. The article also reflects the regulatory documents that served as the basis for the preparation of textbooks in the discipline. When analyzing textbooks and educational-methodological complexes, the authors rely on the stages in the development and formation of the subject and, thus, strive for a methodological analysis of textbooks in the context of the updated content of education, showing the continuity of the development of the content of the subject, and clearly indicating the novelty of the approach. The article provides tables for analyzing the content of textbooks at the primary, basic, senior level of the school. Separate attention is paid to the position of the teacher in teaching self-сognition - an open dialogue between teacher and a pupil in the classroom. The role of the teacher in the formation of the inner and personal concept of “I” of each pupil is special. Thinking with children, rejoicing together, grieving together, learning something new together, being surprised and worried together, which not only creates a positive atmosphere in the classroom, but also helps pupils understand the realities of life. As examples, the authors use some tasks from the textbook and analyze the methodological aspects of new methods of teaching the subject. The research is funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. AP08856223). Key words: updated content of education, self-knowledge, spiritual and moral education, textbook, student’s notebook, methodological guide, content of education.